Sounds of Silence - Tarte, Diane (Queensland Review, 2021)
It was the early 1980s on a warm summer’s evening on North West Island, located in the Capricornia Bunker Group towards the southern end of the Great Barrier Reef. I had some time to myself and was wandering along the beach at sunset. Looking up, I realised there were thousands and thousands, if not hundreds of thousands, of birds — wedge-tailed shearwaters, in fact — circling the island as they returned to their underground nests and their mates and chicks after a day of feeding and cruising the air currents. What was so special about this? After all, it happens every summer’s evening on many Reef sand cays. It was special for me because I suddenly realised that this huge sweep of birds was flying past in total silence … the only sound was an occasional wing dipping into the sea.